UPAYA PENGEMBANGAN BUDIDAYA KERAMBA JARING TANCAP (KJT) DI DANAU KERINCI KECAMATAN DANAU KERINCI KABUPATEN KERINCI - Ferawati, Ferawati; Dasrizal, Dasrizal; Keslan, Widya Prari (STKIP PGRI Sumbar, 2013)
The Thorough this study aimed to obtain the data, process, analyze and discuss: land availability Lake Kerinci, Capital farmed, fish seed and fish feed, Aquaculture development efforts Keramba step (KJT), and of the Government towards the development of Attention Cultivation Keramba step (KJT) .Research methods belong to the descriptive research. The study population was a group of fishermen in Lake Kerinci Kerinci district. Sample of respondents in the study conducted by proportional random sampling technique with 30 % proportion of fishermen, totaling 87 samples .The study results include: 1) views of Lake Kerinci land availability for aquatic activities as many as 150 ha, aquaculture cages to step on the 42 ha, while the new one is about 4 ha utilized. It can be concluded that there is still a lot of land that could be used for activities cages step with the level of achievement of the respondents (77.1 %). 2) The capital required for the manufacture of the cage plots - ie five million Rupiah with the level of achievement of respondents (82.8 %). 3) Fishermen of Lake Kerinci obtain fingerlings and fish feed easily (98.9 %). 4) net cage culture development efforts carried out by the public step by step on the cages to socialize with other people the level of achievement of the respondents (82.8 %). 5) the governments attention to the development of the Cage Aquaculture Fisheries Government Kerinci provide and to provide financial assistance PUMP (Mina Rural Business Development), funding package, fish medicine, the achievement level of the respondents (98.9 %) .